Recovery Motion Analysis for False Ceiling Inspection Robot - Matthew S. K. Yeo; Zhenyuan Yang; S. M. Bhagya P. Samarakoon; R. E. Mohan (Applied Sciences)
The false ceiling plenum is a common and essential part of building infrastructure. However, false ceiling infrastructure requires constant maintenance, which is cumbersome and dangerous for humans since they have to work at high heights and conduct repetitive actions for false ceiling panel replacement. As a solution, robots have been developed to inspect false ceilings. However, these robots can fall during navigation in false ceilings, such as in rugged areas. Therefore, this paper discusses the self-righting capabilities implemented on a false ceiling inspection robot known as FalconX. Mechanisms that aid in self-righting the robot back to a moving position after being toppled due to obstacles within the false ceiling environment were explored, along with their force analysis. Simulations were conducted in Gazebo environments and real hardware experiments were conducted to validate the robot’s self-righting capabilities. The experimental results confirm the self-righting capability of the robot.